Introduction to flat panel displays - Lee, Jiun-Haw; Cheng, I-Chun, 1974-; Hua, Hong, 1973-; Wu, Shin-Tson (Wiley SID series in display technology., 2020)
"Introduction to Flat Panel Displays describes the fundamental physics and materials of major flat panel display technologies including LED, OLED, LCD, PDP and FED and reflective displays. A reference for graduate students and new entrants to the display industry, the book currently covers the basic science behind each display technology and gives solved problems and homework problems in each chapter to aid self-study. With advancements in this field, there is enough change in the FPD industry to justify a second edition. This book offers the latest information on modern display technology and features new developments in OLED materials including phosphorescent, TTA, and TADF OLEDS, white light OLED and light extraction. It provides key information on blue phase, automotive lighting, quantum-dot enhanced LCDS, device configurations and performance, and LEDs, specifically nitrate-based. Application features include OLED for mobile, TV, light and flexible OLED, and reflective display specifically e-paper technology and low power consumption displays"--